Contrast-Induced Sialadenitis of the Sublingual Glands. (8th September 2020) - Park, Ki Wan; Han, Albert Y.; Kim, Christine M.; Tam, Kenric; Chhetri, Dinesh K.
Abstract : Contrast-induced sialadenitis (CIS) is a rare, delayed pseudoallergic reaction from iodine containing contrast. Previously reported cases of CIS demonstrated that the two major salivary glands (parotid and submandibular) can be affected. The initial encounter of this entity can raise alarms to physicians as the differential diagnoses include serious infectious and inflammatory conditions such as Ludwig's angina and angioedema. Subsequently, it may lead to unnecessary testing and increased healthcare cost. Here we present a 60-year-old male who presented with bilateral sublingual gland swelling following exposure to iodinated contrast. With timely diagnosis by the otolaryngologist, the patient received conservative management that led to a full resolution within a few days. To date, this is the first case of CIS only involving the sublingual glands. We conclude that CIS can involve any of the major salivary glands.